Arter Araştirma Programi : 2019. - Öztat, Iz; Ünsal, Merve; Baliç, Ilkay (Istanbul : Arter, 2019)
Iz Öztat & Merve Üsal: Introduction ; Alper Turan: Q is Non-Existent in Turkish ; Ayse Idil Idil: Debt to Memory ; Deniz Aktaş: Silent ; Eser Epözdemir: 10+2 ; Ezgi Tok: Shifting Events and Possible Dilemmas ; Gizem Karakaş: Remembering the Future ; Neslihan Koyuncu: Time Agent ; Nora Tataryan: Things to Say at a Funeral ; Sarp Renk Özer: Technopolitical Cookbook
boek